Risk factors associated with metabolic syndrome in older people in slum areas: a cross-sectional study - Supadmi, Sri; Khairunnisa, Marizka; Kusrini, Ina; Wijanarka, Agus; Kuntari, Titik; Purwoko, Sidiq; Hidayat, Taufiq; Suwarno, Tri; Riyanto, Slamet (Universitas Airlangga, 2025)
Introduction: Older people are at high risk of metabolic syndrome (MetS), non-communicable diseases, and mortality. This makes it difficult for older people in slum areas to achieve healthy and productive quality of life (QOL). In Indonesia, a developing country with a significant and growing number of slum areas, research on this issue remains scarce. This study aimed to analyze the risk factors that play a role in the incidence of MetS in older people living in slum areas. Methods: This was a cross-sectional study. The participants were male and female residents aged ≥45 years, with a total sample size of 150. The participants were selected through simple random sampling from a list of older people. Data analysis was performed using the chi-squared test for bivariate analysis and binary logistic regression for multivariate analysis. Results: The majority of the participants were female (62%), aged between 60-74 years (53.33%), with low-level education (86%), nutritional status in the overweight and obese categories (41.4%), and residence duration <5 years (70%). There was a significant association between district (p < 0.001) and body mass index (BMI) (p < 0.001) with MetS. Overweight participants were more likely to have MetS (AOR 3.75; 95%CI, 1.37-10.24), and the risk was higher among those with obesity (AOR 11.85; 95%CI, 3.90-35.97). Conclusions: The risk of MetS in slum dwellers is higher if they are overweight or obese. Periodic evaluation of body weight can help to control the incidence of MetS.